1970
DOI: 10.1172/jci106256
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-flow studies in man: effect of atrial systole on left ventricular function

Abstract: A B S T R A C T In order to evaluate the effects of atrial contraction on left ventricular function, the pressure gradient technique was used to measure instantaneous aortic blood flow and pressure in nine patients, six having complete heart block and three having normal sinus rhythm. From these data both left ventricular stroke volume and stroke work were calculated. Ventricular rate was controlled by transvenous right ventricular pacing over a range of 50-158 beats/min. At each heart rate, beats which were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The atrial systole is an important determinant of ventricular performance. 38 It has been demonstrated in humans and dogs 35,39,40 that there is a wide range of timings that allows atria and ventricles to work sequentially. However, there is also an optimal PR interval that is associated with the best ventricular hemodynamic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The atrial systole is an important determinant of ventricular performance. 38 It has been demonstrated in humans and dogs 35,39,40 that there is a wide range of timings that allows atria and ventricles to work sequentially. However, there is also an optimal PR interval that is associated with the best ventricular hemodynamic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…13 Incidence of malignant ventricular arrhythmia associated with infarction are changed by the extent of the underlying infarction. 14 Inferior wall myocardial infarction report for 40-50% of all acute myocardial infarction with mortality rates of 2-9%. 15 Bradyarrhythmias occur more frequently in inferior than anterior wall myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell, Gupta, and Payne's work in the dog (12) and reports from this laboratory (8) in patients without mitral valve disease show the absolute increase in stroke volume created by effective atrial systole to be independent of heart rate. In the patient with mild mitral stenosis, we found similar results.…”
Section: )mentioning
confidence: 85%
“…There is a variation among the normals but all exceed the changes seen in those with mitral stenosis. DISCUSSION The importance of atrial contribution to left ventricular function in the experimental animal (9, 10) and in normal humans (8) has been thoroughly evaluated, but little has been written about its significance in rheumatic heart disease and, in particular, pure mitral stenosis. Carleton and Graettinger, using synchronous and sequential atrial pacing, reported effective atrial systole to improve normal human's left ventricular output by 20% but found no effect on individuals with mitral stenosis (1).…”
Section: )mentioning
confidence: 99%